Analisis Implementasi Kebijakan Wajib Sertifikasi Halal bagi Usaha Mikro, Kecil, dan Menengah Sektor Pangan di Kota Pangkalpinang - Sabila, Mifta; Situmeang, Yanti Tesalonika; Alsabilla, Talita Dhea; Lestari, Dwi; Putri, Iyut Rosmita (Consensus : Jurnal Ilmu Hukum, 2025)
The halal industry has become a rapidly growing strategic sector as public awareness of safe, healthy, and Sharia-compliant products increases. As a country with a Muslim majority, Indonesia implements a mandatory halal certification policy based on Law Number 33 of 2014 concerning Halal Product Guarantee (JPH Law), which requires all food products to be halal certified by 2026 at the latest. This study aims to analyze the implementation of the halal certification policy for food MSMEs in Pangkalpinang City and review its law enforcement against business actors who have not complied with these provisions. Using qualitative methods through literature studies, observations, and interviews, the study found that the implementation of halal certification is still hampered by the low level of understanding among MSME actors, limited capital, and procedural complexity. Law enforcement is implemented gradually through socialization, guidance, and administrative and criminal sanctions in accordance with the JPH Law and Government Regulation Number 39 of 2021. In conclusion, halal certification is not only a legal obligation but also a strategic opportunity for MSMEs to enhance competitiveness, expand markets, and strengthen consumer confidence. The successful implementation of  this policy requires effective collaboration between the government, certification bodies, and MSME operators to build an inclusive and sustainable halal industry ecosystem..